Economic Potential of Oil Palm Plantation Using Remote Sensing-Based Technology in Indonesia - Diana, Shinta Rahma; Farida, Farida (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. The productivity of Indonesia's palm oil was considered low when referring to the 14.6 million ha land area in 2019, with the production of national palm oil only reaching 3.2 tons of CPO/ha/year. The uses of remote sensing technology as a means of monitoring and supervising, were expected to increase oil palm production in line with productivity. The purpose of this study was to determine the economic potential based on oil palm plantation productivity, with and without using remote sensing-based technology, as well as other variables likely to affect productivity. Primary and secondary data collection methods were also used in this research. There were three quantitative methods being used in this study, namely (i) Multiple regression model with panel data, (ii) Data Envelopment Analysis (DEA) tool, and (iii) Multinomial logistic regression technique. The results showed that the generated economic potential from the utilization of the remote sensing model, had efficient opportunity value of 10.48, which was higher than the non-usage of the technology.  Therefore, the main variables that affected productivity in this study, were fertilizer and labour. Keywords: Efficiency, oil-palm, remote sensing (spot 6), policy, binomial logistic